2017
DOI: 10.1152/ajpheart.00209.2017
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes primitive glycosaminoglycan-rich extracellular matrix composition in developing heart valves

Abstract: During postnatal heart valve development, glycosaminoglycan (GAG)-rich valve primordia transform into stratified valve leaflets composed of GAGs, fibrillar collagen, and elastin layers accompanied by decreased cell proliferation as well as thinning and elongation. The neonatal period is characterized by the transition from a uterine environment to atmospheric O, but the role of changing O levels in valve extracellular matrix (ECM) composition or morphogenesis is not well characterized. Here, we show that tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…While hypoxia is known to regulate collagen as well as glycosaminoglycans in AVs (8, 27), its effects on elastin is not known. We observed fragmented elastic fibers in the ventricularis of both 20 and 13% O 2 AVs compared to fresh AVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While hypoxia is known to regulate collagen as well as glycosaminoglycans in AVs (8, 27), its effects on elastin is not known. We observed fragmented elastic fibers in the ventricularis of both 20 and 13% O 2 AVs compared to fresh AVs.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated the effects of hypoxia in aged AVs. Given that almost all studies that investigated role of hypoxia in valve disease employed valves from young animals (5, 8, 27), our major goal was to study aged AVs from pigs and humans to gain better insights on the influence of hypoxia on valve disease. We sought to study porcine AVs because pigs have been shown to be a good model to study heart valve diseases.…”
Section: Discussionmentioning
confidence: 99%
“…At P7, the formation of a collagen layer starts to be detected in valve leaflets ( Fig. 1A, black arrowheads), in contrast to its low expression at P1 (Amofa et al, 2017), but the primitive leaflets remain thickened ( Fig. 1A).…”
Section: Heterogeneity Of P7 and P30 Heart Cells Is Revealed By Droplmentioning
confidence: 99%
“…At P30, valve leaflets are elongated with regionalized distribution of fibrillar collagen and proteoglycan ( Fig. 1A) (Amofa et al, 2017). Single cell isolations from aortic and mitral valve leaflets were obtained from valves dissected from P7 and P30 mouse pups, which were pooled and dissociated to obtain single cell suspensions.…”
Section: Heterogeneity Of P7 and P30 Heart Cells Is Revealed By Droplmentioning
confidence: 99%
“…The membrane was blocked in 5% milk/TBST for 1 hour and probed with rabbit anti-mouse polyclonal HYAL2 antibody diluted to 1:500 (Abcam #68608; Cambridge, UK) overnight at 4 °C. This antibody has been used to detect HYAL2 in human aortic valve interstitial cells cultured in hypoxia 34 . SOD3 from HPASMCs was probed with mouse-anti-human monoclonal antibody (sc-376948, Santa Cruz Biotech; Dallas, TX).…”
Section: Rt-qpcr For Ha-regulating Gene Expressionmentioning
confidence: 99%